[PP.30.14] SALT CONSUMPTION IN CROATIAN CONTINENTAL RURAL POPULATION: ENAH STUDY. (September 2016) - Karanovic, S.; Vrdoljak, A.; Ivkovic, V.; Dika, Z.; Domislovic, V.; Dapic, K.; Gallineo, L.; Ivandic, E.; Josipovic, J.; Vukovic, I.; Kos, J.; Laganovic, M.; et al.
Abstract : Objective: Results from our previous survey confirmed that salt consumption (24 h mapping) in Croatia is above 11 g/day. Salt intake was higher in rural than in urban area. Croatian national campaign started in 2008 and our aim was to analyze trends in salt consumption in rural area in the past period. Design and method: Out of 3056 subjects enrolled in ENAH study, 2259 (868m, 1391w) were eligible for further analysis. All inhabitants older than 18 years of age from this rural area were invited to participate and were examined on a door-to-door basis. Pregnant women, patients with terminal illness who were bed-ridden, patients with severe disability or those who have had at least one limb amputated or immobilized and mentally ill or suffering from dementia were considered ineligible. Participation rate was >70%. Salt intake (g/day) was estimated from the first morning spot urine using Intersalt equation. Blood pressure (BP) was measured using Omron 6 device following the ESH guidelines. Villagers were examined in 2008, 2010 and 2015 and trends in salt intake and association with BP were analyzed. There were no differences in age and gender between survey years. Results: In 2008, 2010, 2015 salt intake in the whole group was 10.5(8.7–12.2); 10.2(8.4–12.1); 10.9 (9.5–12.2), respectively; in men 10.4(8.8–12.2); 10.1(8.5–12.1);10.9 (9.3–12.3), respectively; in women 10.6 (8.6–12.3); 10.4(8.4–12.1); 10.9 (9.6–12.1), respectively. We failed to observe trend in decreasing salt intake, without gender difference. Significant correlation between salt intake and systolic and diastolic BP was found in the whole group (r = 0.32; r = 0.18, respectively, both p < 0.001), in men(r = 0.29; r = 0.134, respectively, both p = 0.01) and in women (r = 0.35; r = 0.21, respectively, both p < 0.001). Conclusions: We are fully aware of many drawbacks related to the spot urine sampling. However, using the same method and the same equation in the same population we believe that we can consider our results reliable to estimate the trend of salt consumption in rural area. Significant correlation with BP was observed which confirms prior results. Despite of the Croatian National Program launched 10 years ago, salt consumption in rural area is very high and remains unchanged and further efforts in this field are needed.